The Effect of Practise Method and Motor Ability on Improving Complex Motor Skill in Football Games - Reki Siaga Agustina; Agus Mahendra; Tite Juliantine (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
This study was aimed at determining the interaction of training methods (distributed practice and massed practice) and motor ability on complex motor skills in soccer. This study used experimental method with factorial design 2x2. The research samples were 28 people. The motor ability data were obtained by using the motor barrow ability test. To measure complex motor skills, the Wall Volley-Test was used. Data analysis technique used variance analysis 2 way design and hypothesis testing was conducted by using tukey test at the significance level α = 0.05. The results of the study conclude that there was a significant interaction effect between training methods and motor abilities on increasing complex motor skills in soccer. Athletes who have high motor abilities are better to have distributed practice exercises. Meanwhile, athletes who have a low motor ability is better to get training in massed practice